The roadmap 2030 Study: A Survey of Teachers, Subject Leaders and University Lecturers on the Situation and Perspectives of Geography as a School Subject - Fögele, Janis; Mehren, Rainer; Thume, Sandra (Journal of Geography Education, 2025)
As part of the roadmap 2030 initiative, teachers, subject leaders, and university lecturers of geography education in Germany were surveyed on six topics, including the development of geography as a school subject, textbooks, continuing education, and curricula. The article analyzes the differences between the groups surveyed and shows a broad consensus in their assessment of the current situation. Particular emphasis is placed on the loss of importance of the school subject, caused by cuts in teaching hours, structural disadvantages, and teaching outside the subject. Recommendations for the future include better lobbying, more freedom in the curricula, greater geodigitization, and the upgrading of scientific content.